Legitimation, institutions and regional path creation: a cross-national study of offshore wind. Issue 4 (3rd April 2022) - MacKinnon, Danny; Karlsen, Asbjørn; Dawley, Stuart; Steen, Markus; Afewerki, Samson; Kenzhegaliyeva, Assiya
ABSTRACT: This paper assesses legitimation as a crucial dimension of industry emergence, addressing the neglect of institutional and political aspects of path creation in economic geography. It investigates how the legitimacy of emerging industries is built up over time and examines differences in legitimation across space. The paper focuses on the evolution of legitimation narratives in the context of national and regional differences in institutions, actors and assets. Based on a cross-national study of the offshore wind industry, the paper argues that cost reduction and value creation have made important contributions to legitimation in addition to climate change and energy security.